Circuit Contributions to Sensory-Driven Glutamatergic Drive of Olfactory Bulb Mitral and Tufted Cells During Odorant Inhalation - Moran, Andrew K.; Eiting, Thomas P.; Wachowiak, Matt (Frontiers in Neural Circuits, 2021)
In the mammalian olfactory bulb (OB), mitral/tufted (MT) cells respond to odorant inhalation with diverse temporal patterns that are thought to encode odor information. Much of this diversity is already apparent at the level of glutamatergic input to MT cells, which receive direct, monosynaptic excitatory input from olfactory sensory neurons (OSNs) as well as a multisynaptic excitatory drive via glutamatergic interneurons. Both pathways are also subject to modulation by inhibitory circuits in the glomerular layer of the OB. To understand the role of direct OSN input vs. postsynaptic OB circuit mechanisms in shaping diverse dynamics of glutamatergic drive to MT cells, we imaged glutamate signaling onto MT cell dendrites in anesthetized mice while blocking multisynaptic excitatory drive with ionotropic glutamate receptor antagonists and blocking presynaptic modulation of glutamate release from OSNs with GABAB receptor antagonists. GABAB receptor blockade increased the magnitude of inhalation-linked glutamate transients onto MT cell apical dendrites without altering their inhalation-linked dynamics, confirming that presynaptic inhibition impacts the gain of OSN inputs to the OB. Surprisingly, blockade of multisynaptic excitation only modestly impacted glutamatergic input to MT cells, causing a slight reduction in the amplitude of inhalation-linked glutamate transients in response to low odorant concentrations and no change in the dynamics of each transient. The postsynaptic blockade also modestly impacted glutamate dynamics over a slower timescale, mainly by reducing adaptation of the glutamate response across multiple inhalations of odorant. These results suggest that direct glutamatergic input from OSNs provides the bulk of excitatory drive to MT cells, and that diversity in the dynamics of this input may be a primary determinant of the temporal diversity in MT cell responses that underlies odor representations at this stage.